Policy of the Coastal Zone and Small Islands Zoning Plan (RZWP3K) Viewed Through the Perspective of Fiqhiyah Rules: Kebijakan Rencana Zonasi Wilayah Pesisir dan Pulau-Pulau Kecil (RZWP3K) ditinjau Melalui Perspektif Kaidah Fiqhiyah - Junaidi, M.; Nugroho, Wisnu Tri; Jannah, Roudlotul (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to investigate the challenges within the policy of coastal zoning plan and small islands (RZWP3K) from legal, social, environmental, and fiqh perspectives, while proposing concrete solutions to address implementation issues. Employing a juridist-normative approach, the study reveals that while RZWP3K is intended to spur economic development and regulate coastal areas, it often neglects aspects of sustainable development, leading to exploitation of marine resources and neglect of coastal communities' rights. Despite its noble intentions, irregularities within the policy hinder its effectiveness, resulting in limited impact on coastal community welfare. Drawing on Fiqhiyyah principles such as sad adz-Dzari'ah and Fath Adz-Dzariah, the study advocates for legislative amendments to rectify existing weaknesses and ensure equitable implementation, thus promoting sustainable coastal management and community well-being. Highlights: Comprehensive analysis: Investigating coastal zoning policy challenges from legal, social, environmental, and fiqh perspectives. Implementation issues: Identifying irregularities hindering effective policy implementation and their impact on coastal communities. Fiqhiyyah solutions: Proposing amendments informed by Fiqhiyyah principles to promote equitable implementation and sustainable coastal management. Keywords: Principles of Fiqhiyah, RZWP3K Policy, Government.